Characterization of microbiomic and geochemical compositions across the photosynthetic fringe - Weeks, Katelyn; Trembath-Reichert, Elizabeth; Boyer, Grayson; Fecteau, Kristopher; Howells, Alta; De Martini, Francesca; Gile, Gillian H.; Shock, Everett L. (Frontiers in Microbiology, 2023)
Hot spring outflow channels provide geochemical gradients that are reflected in microbial community compositions. In many hot spring outflows, there is a distinct visual demarcation as the community transitions from predominantly chemotrophs to having visible pigments from phototrophs. It has been hypothesized that this transition to phototrophy, known as the photosynthetic fringe, is a result of the pH, temperature, and/or sulfide concentration gradients in the hot spring outflows. Here, we explicitly evaluated the predictive capability of geochemistry in determining the location of the photosynthetic fringe in hot spring outflows. A total of 46 samples were taken from 12 hot spring outflows in Yellowstone National Park that spanned pH values from 1.9 to 9.0 and temperatures from 28.9 to 92.2 ℃. Sampling locations were selected to be equidistant in geochemical space above and below the photosynthetic fringe based on linear discriminant analysis. Although pH, temperature, and total sulfide concentrations have previously been cited as determining factors for microbial community composition, none of these factors significantly correlated with microbial community composition in the NMDS analyses. Additionally, there was no observed statistical significance between beta diversity and the relative position to the photosynthetic fringe. Dissolved inorganic and organic carbon concentrations correlated with overall microbial community composition with statistical significance according to NMDS analyses, but also correlated with pH and temperature, making it difficult to separate their roles in determining microbial community composition. In the co-occurrence network analyses, each clique correlated with either pH and/or temperature, whereas sulfide concentrations only correlated with individual nodes These results indicate that there is a complex interplay between geochemical variables and the position of the photosynthetic fringe that cannot be fully explained by statistical correlations with the individual geochemical variables included in this study.